Analisis Pelaksanaan Zona Integritas di Kepolisian Resor Ternate Guna Terwujudnya Wilayah Bebas dari Korupsi - Wresni Haryadi; Abdul Rahman Jannang; Rahmat Sabuhari (Peneliti.net, 2022)
Analysis of the Implementation of the Integrity Zone at the Ternate Police for the Realization of a Corruption-Free Area